2012
DOI: 10.1099/vir.0.046672-0
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular stomatitis virus as a flexible platform for oncolytic virotherapy against cancer

Abstract: Oncolytic virus (OV) therapy is an emerging anti-cancer approach that utilizes viruses to preferentially infect and kill cancer cells, while not harming healthy cells. Vesicular stomatitis virus (VSV) is a prototypic non-segmented, negative-strand RNA virus with inherent OV qualities. Antiviral responses induced by type I interferon pathways are believed to be impaired in most cancer cells, making them more susceptible to VSV than normal cells. Several other factors make VSV a promising OV candidate for clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
174
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(180 citation statements)
references
References 151 publications
2
174
0
Order By: Relevance
“…Hastie & Grdzelishvili published an excellent overview of abovementioned strategies and resulting oncolytic VSVs in 2012. 88 A recent study in purpose-bred beagle dogs showed that a dose up to 10 10 TCID 50 of VSV-hIFNb was well tolerated, with mild adverse events with the exception of one dog that received 10 11 TCID 50 which developed severe hepatotoxicity and shock leading to euthanasia. 93 A following study testing VSV-hIFNb on rhesus macaques via intrahepatic injection did not result in neurological symptoms and is considered to be safe enough to proceed into phase I clinical trials, which are currently ongoing in humans and pet dogs.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
See 4 more Smart Citations
“…Hastie & Grdzelishvili published an excellent overview of abovementioned strategies and resulting oncolytic VSVs in 2012. 88 A recent study in purpose-bred beagle dogs showed that a dose up to 10 10 TCID 50 of VSV-hIFNb was well tolerated, with mild adverse events with the exception of one dog that received 10 11 TCID 50 which developed severe hepatotoxicity and shock leading to euthanasia. 93 A following study testing VSV-hIFNb on rhesus macaques via intrahepatic injection did not result in neurological symptoms and is considered to be safe enough to proceed into phase I clinical trials, which are currently ongoing in humans and pet dogs.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
“…91,92 All 3 strategies previously described (conditional replication, arming, and targeting) have been employed to increase efficacy of VSV. 88 Furthermore, combination therapy has been described with different other therapies. Finally, optimizing delivery and distribution of oncolytic VSVs has been evaluated using cell-based carriers and aptamer or PEGylation of virions.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
See 3 more Smart Citations